Developments in optimizing transperineal prostate biopsy. Issue 1 (15th January 2022) - Cheng, Emily; Davuluri, Meenakshi; Lewicki, Patrick J.; Hu, Jim C.; Basourakos, Spyridon P.
Abstract : Purpose of review: Prostate biopsy is a very commonly performed office procedure leading to the diagnosis of the most prevalent solid-organ malignancy in American men. Although the transrectal technique for prostate biopsy remains the gold standard, there is increasing interest in the transperineal approach as it offers a clean, percutaneous approach that significantly decreases the risk for infection. In this review, we discuss emerging developments in transperineal prostate biopsy that may optimize the way biopsies are performed in clinical practice. Recent findings: Similarly, to transrectal biopsy, the transperineal approach also allows for the performance of systematic and MRI-targeted biopsy cores. As transperineal biopsy obviates the translocation of rectal bacteria to the prostate or bloodstream, in contrast to transrectal biopsy, it is feasible to forgo peri-procedural antibiotics in accordance with professional guidelines. This may attenuate antimicrobial resistance that may be associated with augmented prophylaxis. In addition, although transperineal biopsy may be traditionally performed under general anesthesia using a template grid, it may also be performed freehand under local anesthesia or sedation. Avoiding prophylactic antibiotics and general anesthesia as well as reducing infections/hospitalizations for transperineal biopsy scaled nationally will likely result in significant healthcare savings. Summary: Transperineal biopsy with combined systematic and MRI-targeted cores, offers several advantages over conventional transrectal biopsy. Transperineal biopsy under local anesthesia and without periprocedural antibiotic is emerging as a promising method for prostate cancer diagnosis and surveillance.